A biblioteca como espaço de formação da consciência leitora - Rosa, Rosirene Dias (2022)
The purpose of this work is to identify the importance of the library space in the literacy process in the formation of reading students at Colégio Estadual Jardim América. Therefore, we seek to understand reading as a movement that provides moments of leisure, as well as an indispensable tool for the constitution of a society with the capacity to be free and active. For this we need to understand the importance of reading and the School Library in the formation of the future reader and the practices of reading and writing with emphasis on literary texts, or specifically on literary literacy. Thinking about this student/subject/reader and about the pedagogical practice of basic education teachers, we started to analyze the importance of the library in the construction and evolution of human thought. The study used interviews with the manager responsible for the school libraries of the Secretaria de Estado da Educação de Goiás, SEDUC, and language teachers at Colégio Estadual Jardim mérica, using the exploratory method, of a qualitative nature, based on of documental study with a survey of the main policies, projects and actions on school libraries at SEDUC and projects developed in the area of languages that in fact have contributed to the formation of student readers, using the analysis of the interviews of the Content Analysis Method, in the first chapter; in the second, we have an approach to the school library, covering its dimension and, in the third chapter, we illustrate the research, with a brief analysis of the book A Biblioteca Mágica the Bibbi Bokken.